2023
DOI: 10.3390/horticulturae9040504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Water Treatment on the Growth, Nutritional Status, and Yield of Lettuce Plants with Irrigation Rate

Abstract: Climate change is causing an increase in dry spells, altering rainfall patterns and soil moisture, and affecting water and nutrient plant uptake, which inevitably affects vegetable production. To mitigate this issue, some technologies that allow the maintenance of the ideal soil moisture for the uptake process are being investigated. Considering this, we hypothesize that the use of water treated with a magnetic field can increase water use efficiency in lettuce crop production. Thus, the present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The increase in production parameters found in lettuce irrigated with magnetically treated water corroborates several surveys that describe technology with a high potential of reducing the volume of water applied, such as in the cultivation of celery, green beans and peas [60]; chickpeas [61]; castor beans [62]; corn [63]; tobacco [64]; peas [65]; tomatoes [66,67]; wheat [68]; and pepper [69]. Putti et al [70] also reported the beneficial effects of magnetically treated water on lettuce plants due to improvement in nutritional status and yield. However, when lettuce was irrigated with magnetically treated water, among the parameters analyzed, the leaf number and fresh shoot biomass showed a significant reduction along the crop cycle, reaching the same values when lettuce was irrigated with conventional water.…”
Section: Discussionsupporting
confidence: 78%
“…The increase in production parameters found in lettuce irrigated with magnetically treated water corroborates several surveys that describe technology with a high potential of reducing the volume of water applied, such as in the cultivation of celery, green beans and peas [60]; chickpeas [61]; castor beans [62]; corn [63]; tobacco [64]; peas [65]; tomatoes [66,67]; wheat [68]; and pepper [69]. Putti et al [70] also reported the beneficial effects of magnetically treated water on lettuce plants due to improvement in nutritional status and yield. However, when lettuce was irrigated with magnetically treated water, among the parameters analyzed, the leaf number and fresh shoot biomass showed a significant reduction along the crop cycle, reaching the same values when lettuce was irrigated with conventional water.…”
Section: Discussionsupporting
confidence: 78%
“…Further studies may be needed to explore the long-term effects of magnetic water treatment on soil pH dynamics and its implications for plant growth and nutrient availability. Some studies have indeed reported slight increases in soil pH following magnetic water treatment [42,43] and other studies reported a reduction of the pH in the soil with magnetic treatment [44].…”
Section: Chemical Properties Of the Experimental Soilmentioning
confidence: 97%